2018
DOI: 10.14393/bj-v34n1a2018-37238
|View full text |Cite
|
Sign up to set email alerts
|

Investigating lead and zinc uptake and accumulation by Stipa hohenackeriana trin and rupr. in field and pot experiments

Abstract: This study was conducted to evaluate Pb and Zn uptake, mobility, and accumulation in Stipa hohenackeriana using field soil in pot and field experiments. Moreover, the effects of Municipal Solid Waste Compost (MSWC) (0, 1, and 2%) and Nano-Silica (NS) (0, 250, and 500 mg/kg) on Stipa biomass, Pb and Zn availability in the soil, and Pb and Zn uptake and accumulation were studied using pot experiments. Samples of soil, root, and shoots of Stipa were collected from field and greenhouse and after drying, extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Total Chlorophyll (TCh) (The amount of chlorophyll in plant leaves was measured by a chlorophyll meter) 26 , leaf area index (LFA) (leaf area index was measured based on ground based method) 27 , relative water content (RWC) 28 and biological yield (BY) 29 were evaluated www.nature.com/scientificreports/ in this study. For this purpose, in the end of growth stage, 3 plants from each plot were randomly selected 30,31 . Summary of statistical indices for estimated characteristics are shown in Table 2.…”
Section: Study Area and Climatic Characteristicsmentioning
confidence: 99%
“…Total Chlorophyll (TCh) (The amount of chlorophyll in plant leaves was measured by a chlorophyll meter) 26 , leaf area index (LFA) (leaf area index was measured based on ground based method) 27 , relative water content (RWC) 28 and biological yield (BY) 29 were evaluated www.nature.com/scientificreports/ in this study. For this purpose, in the end of growth stage, 3 plants from each plot were randomly selected 30,31 . Summary of statistical indices for estimated characteristics are shown in Table 2.…”
Section: Study Area and Climatic Characteristicsmentioning
confidence: 99%
“…Similarly, SiO 2 application to M. sativa increased plant height, tiller count, yield, FW, and DW, chlorophyll content, and carotenoid levels ( Ma and Yamaji, 2006 ; Zmeeva et al, 2017 ). Govorov and Carmeli (2007) reported that SiO 2 NPs increase leaf FW and DW as well as chlorophyll content in O. basilicum , and also negatively affect shoot and root growth in S. bicolor , Stipa hohenackeriana , and Secale montanum ( Lee et al, 2012 ; Moameri et al, 2018b ; Moameri and Abbasi Khalaki, 2019 ). ZnO NPs increase biomass, root and shoot length, and chlorophyll content in many plant species ( Peyvandi et al, 2011b ; Raliya and Tarafdar, 2013 ; Najafi Disfani et al, 2017 ; García-López et al, 2018 ; Yuan et al, 2018 ).…”
Section: Npsmentioning
confidence: 99%
“…Siddiqui et al (2007) reported that SiO2 increased leaf fresh and dry weight and chlorophyll content in Ocimum basilicum. SiO2 NP application was found to affect shoot and root growth negatively in Sorghum bicolor, Stipa hohenackeriana and Secale montanum plants (Lee et al, 2012;Moameri et al, 2018b;Moameri and Abbasi Khalaki, 2019).…”
Section: Nanoparticlesmentioning
confidence: 99%